Female income differentials and social benefits: A four country comparison - Eva Sierminska (Luxembourg Income Study (LIS), 2004)
Past literature on the family gap - the difference in outcomes for mothers and women without children - discusses inequality in wages and employment. This study examines family gaps in the economic well-being of households, and analyzes the extent to which they are reduced by the availability of social benefits. Preliminary results, using the Luxembourg Income Study, indicate that the generosity of the social protection system accounts for the size of the family gap, particularly in countries with sizeable income differentials. In countries with the most generous systems, family gaps for the lower half of the income distribution are, to begin with, very small. The inequality analysis finds that earnings have a significant role in determining overall inequality due to their large share in total income. Benefits have a redistributive effect in all countries, with the magnitude of this effect depending on the generosity of benefits relative to income.
Keywords: 330; Weibliche Arbeitskräfte; Familienleistungsausgleich; Haushaltseinkommen; Kinder; Schweden; Frankreich; Polen; USA